PELAKSANAAN ROYA PARSIAL DI KANTOR PERTANAHAN KABUPATEN GIANYAR TERHADAP HAK TANGGUNGAN BAGI PENGEMBANG YANG MENERIMA KREDIT KONSTRUKSI BPR SUKAWATI PANCAKANTI KABUPATEN GIANYAR - Wisnu Saputra, I Made; -, Adiwati; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014)
Implementation of housing and residential development undertaken by private developers organized. In doing the residential development business, developers need support from banks as creditors which gives a construction loan. As collateral to get a construction loan from the bank, the developer can use the location of land to be built housing project, following the buildings that will be erected on the land. Simultaneously when the developers doing development, developers can directly make sales units built houses to home buyers, buyers in making purchase of housing units from the developer, the payment can be by cash or credit. With the unsold units, then the developer should be split parent certificate for a certificate per housing unit on behalf of the buyer. Because the burden of mortgage certificates, then to split certificates per unit on behalf of the buyer, must go through roya partial or partial removal of the mortgage. Based on the real nature of the law or in accordance with the reality of life in the community. BPR issued a roya partial on housing units that are paid to the developer can then split the certificate to the land office.
Keywords: Construction Loan, Mortgage, Roya Partial